The unsung heroes in the fight to end HIV: The role of nurses in Indonesia - Kusman Ibrahim, S. Kp., MNS., PhD.; Erin M. Kahle (Faculty of Nursing Universitas Padjadjaran, 2024)
HIV new cases are continuing to be reported in Indonesia. Although progress in HIV prevention and control has been made, Indonesia continues to face significant challenges in its fight against HIV. Continued efforts to expand treatment, reduce stigma, and strengthen prevention initiatives by involving health care workers and all stakeholders are essential to controlling the epidemic and improving the lives of those affected by HIV in the country. As a healthcare worker, nurses are central to the country's efforts to control and eventually end the HIV epidemic. Their roles are diverse and impactful, ranging from direct patient care to community outreach, education, and policy advocacy. As Indonesia continues to face challenges in its HIV response, the contributions of nurses will remain essential in overcoming these barriers and improving the lives of those affected by HIV.